2019
DOI: 10.1097/corr.0000000000000739
|View full text |Cite
|
Sign up to set email alerts
|

Does Three-dimensional Printing Plus Pedicle Guider Technology in Severe Congenital Scoliosis Facilitate Accurate and Efficient Pedicle Screw Placement?

Abstract: Background Three-dimensional (3-D) printing offers the opportunity to create patient-specific guides for pedicle screw placement based on CT-generated models. This technology might allow for more-accurate placement of pedicle screws in patients with severe congenital scoliosis who have rotated vertebrae and small pedicles, but to our knowledge, this premise has not been tested. Questions/purposes (1) Is the use of 3-D printing and pedicle guider technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 23 publications
0
49
0
9
Order By: Relevance
“…In our review, 3DP applications, including 3DP screw guides and planning models, have resulted in statistically decreased operative durations and increased pedicle screw placement accuracy. 1,18,19,28,31 Compared with conventional imaging (eg, intraoperative fluoroscopy), 3DP screw placement guides provide improved screw placement accuracy rates, 19,20,[31][32][33][34][35] and models enhance intrateam communication and planning, 21,[23][24][25]28,36 and reduced fluoroscopy time. 19,20 In one retrospective study of 126 adolescent idiopathic scoliosis patients with a Lenke 1 deformity, Yang et al 1 showed that 3DP models used for surgical planning resulted in reduced operative duration and blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…In our review, 3DP applications, including 3DP screw guides and planning models, have resulted in statistically decreased operative durations and increased pedicle screw placement accuracy. 1,18,19,28,31 Compared with conventional imaging (eg, intraoperative fluoroscopy), 3DP screw placement guides provide improved screw placement accuracy rates, 19,20,[31][32][33][34][35] and models enhance intrateam communication and planning, 21,[23][24][25]28,36 and reduced fluoroscopy time. 19,20 In one retrospective study of 126 adolescent idiopathic scoliosis patients with a Lenke 1 deformity, Yang et al 1 showed that 3DP models used for surgical planning resulted in reduced operative duration and blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Although 3D printing assisted guide plates have been diffusely applied in clinical correction researches of cubitus varus deformity, developmental dysplasia of the hip, spinal scoliosis, hallux valgus and other deformities [17][18][19][20], while the application in ATE malformation correction has been rarely reported. Previously, Windisch et al [21] applied 3D printing technology to fabricate a physical model of ATE malformation with a magnification of 4 times for surgeons to accurately analyze all bone and joint deformities, and perform preoperative planning, but this application only played the most basic role of 3D printing.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Luo et al demonstrated that accuracy of the surgical technique using spinal 3D printing technology in patients with severe congenital scoliosis was higher than that of the free-hand technique, and it appeared to shorten operative time. [22] It is reported that the intraoperative navigation system or robotic assistant system have been used to enhance the accuracy of pedical screw insertion in the treatment of spine degenerative and some spine deformity disease, [23] and it turns out to be fesiable and effective. [24,25] However, in severe spine deformity surgery, the evidence was unpowered and insu cient.…”
Section: Discussionmentioning
confidence: 99%